Hematoma Evacuation Outcome in Patients with Spontaneous Supratentorial Intracerebral Hemorrhage - Robert Sinurat; Ahmad Faried (Majalah Kedokteran Bandung, 2022)
The mortality rate of spontaneous supratentorial intracerebral hemorrhage evacuation is still high and varies in all neurosurgical centers. Currently, minimally invasive surgery to evacuate bleeding has become an option, but not all neurosurgical centers can perform the procedures due to limited resources. In addition, there are several guidelines for determining which patients will undergo a surgery. This study assessed the outcome of selected patients who were operated on using micro neurosurgical procedures or external ventricular drainage for intraventricular hemorrhage between 2016 and 2021. Patients included in this study were recruited from a hospital in Jakarta, Indonesia and  selected based on the guideline of the 2015 American Heart Association/American Stroke Association (AHA/ASA). The outcome was assessed by a modified Rankin scale (mRS). There were 301 patients with hemorrhagic stroke but only fifty patients were matched the criteria in the guideline. Male patients constituted the majority of the patients (n=28, 56%) and hypertension has occurred in 37 (74%) patients. The hematoma was mostly located in the intracerebral with intraventricular extension (n=27, 54%) patients. The pre-operative Glasgow Coma Scale (GCS) of 23 (46%) patients were comatose and the other was 9–13. Postoperatively, there were 37 (74%) patients with a scale of 13–15, but 10 (20%) patients died. Pair t-test of the preoperative and postoperative scales showed a significant difference, p < 0.01. The outcome of 40 (80%) patients was good (modified Rankin scale of 0–3), and the Spearman’s rank correlation coefficient was -0.739 with the Sig.2-tailed was <0.01. The outcome of spontaneous supratentorial intracerebral hemorrhage evacuation is good when selecting patients following the 2015 AHA/ASA guideline and there is a strong correlation between postoperative GCS with 3-month mRS results.